Dynamics of the transcriptome during chicken embryo development based on primordial germ cells - Aleksandra Dunislawska (BMC Research Notes, 2020)
Abstract Objective Regulation of gene expression during embryo development on the basis of migration of primordial germ cells (PGCs) in vivo has been rarely studied due to limited cell number and the necessity to isolate PGCs from a large number of embryos. Moreover, little is known about the comprehensive dynamics of the transcriptome in chicken PGCs during early developmental stages. The current study investigated transcriptome dynamics of chicken PGCs at key developmental stages: 4.5, 8 and 12 days of embryo incubation. PGCs were collected, and RNA was isolated using a commercial kit for single cells. The isolated RNA was subjected to microarray analysis (Agilent Technologies). Results Between 8 and 12 days of incubation, the highest number of genes was regulated. These data indicate that the most intense biological activity occurs between 8 and 12 days of embryo development. Heat map showed a significant decrease in gene expression on day 8, while it increased on day 12. The development of a precise method to isolate bird PGCs as well as the method to isolate RNA from single cells isolated from one embryo allows for early molecular analysis and detection of transcriptome changes during embryonic development.